Dialog Konstitusional sebagai Mekanisme Non-Litigasi dalam Resolusi Konflik Sosial: Peran Pendidikan Kewarganegaraan dalam Internalisasi Nilai Konstitusi - Ichwani Siti Utami (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
The escalation of social conflicts in Indonesia reflects a communication crisis between the state and society within the democratic sphere. Demonstrations that end in physical clashes indicate the weakness of deliberative dialogue culture and the inadequate internalization of constitutional values in democratic life. This article aims to analyze Constitutional Dialogue as a non-litigation mechanism for resolving social conflicts and to examine the role of Civic Education in internalizing constitutional values. This study employs a literature review method with juridical-normative and conceptual approaches through the examination of deliberative democracy theory, constitutional dialogue, relevant legal norms, and related academic literature. The findings reveal that the failure of social conflict resolution is influenced not only by weak legal structures, but also by the absence of a participatory and deliberative public dialogue culture. Constitutional Dialogue offers a more inclusive, empathetic, and collaborative mechanism for conflict resolution. In this regard, Civic Education plays a strategic role in fostering civic virtue, legal awareness, and citizens’ dialogic competence to strengthen a participatory and civilized constitutional democracy.